Interaction Between LncRNA and UPF1 in Tumors - He, Junjian; Ma, Xiaoxin (Frontiers in Genetics, 2021)
Long noncoding RNAs (LncRNAs) can bind to other proteins or RNAs to regulate gene expression, and its role in tumors has been extensively studied. A common RNA binding protein, UPF1, is also a key factor in a variety of RNA decay pathways. RNA decay pathways serve to control levels of particular RNA molecules. The expression of UPF1 is often dysregulated in tumors, an observation which suggests that UPF1 contributes to development of a variety of tumors. Herein we review evidence from studies of fourteen lncRNAs interact with UPF1.The interaction between lncRNA and UPFI provide fundamental basis for cell transformation and tumorigenic growth.